Fluctuations in The Burrow Intensity of Sympatric Murids in Relation to Different Crops At Village Kakrod Jind (HARYANA) - Kumar, Parmesh; Pashan, S C (Annals of Arid Zone, 2016)
Data analysis revealed relationship between the burrow intensity fluctuations and the advancement of crop growth. At the seedling stage of cotton, Jowar, bajra and guar 7 to 13.6 burrows of different murids were recorded. The number graduallyincreased to 25.2 - 42 by the time crops attained their maturity. At seedling stage most of burrows were concentrated on the periphary while at maturity stage majority of the burrows were shifted to inside crop fields. Like kharif crops, in rabi crops too a low burrow intensity of 7 to 9 burrows was recorded at the seedling stage of wheat and gram. The burrow intensity increased with the advancement in crop growth and reached its peak (average 35 to 46 burrows) at the maturity stage.